A Mind Prober as a Metaphor. Of Solar, of Visual, of Parabolic, of Comic, and of Punk Mind - Płuciennik, Jarosław (Zagadnienia Rodzajów Literackich, 2022)
This is an introduction to a special issue of Issues of Literary Types, which has no special topic. The author of the introduction reflects on the metaphor of the mind prober used to define a genre of a topic-free issue of a scientific journal. In the case of a scientific journal, the research area is strictly defined, as in the case of thematic issues: the area is defined by the leading subject matter. It is different in the case of an issue without a topic: the area is outlined, but what topics will stand out in the foreground depends on the current state of the collective mind. In this context, a probe as a tool for examining the collective mind of a group is an extremely attractive metaphor. One computer game program was called “Mind Prober”. It tried to determine a gamer’s personality and give advice based on the gamer’s answers to questions. It is described as an early self-analysis program. We obviously live in the sentimental era as defined by Schiller in an essay called Naive and sentimental. We can define our time by our hopes and dreams such as solarpunk. We can refer to comedy as a genre which is better than tragedy or apocalyptic. Parabole, isomorphism in multimodality, projecting and invisible: they are all genre-like states of mind which might characterize our situation confronting crises and catastrophes.